In vitro effects of prostaglandin F2? and metamizol on motility of diluted bull semen - Karahan, İ; Türk, G; Gür, S (My University, 2006)
The purpose of the present study was to investigate in vitro effects of prostaglandin F2 alpha (PGF2a) and metamizol on the motility of diluted bull semen during short-term storage at 4 ¼C. In this study, 3 healthy adult Brown-Swiss bulls, each 3 years old, were used. Semen samples were collected with an artificial vagina. Samples were taken from each bull twice a week over the course of 3 weeks (6 samples per bull). One millilitre of semen was removed from each sample for the determination of semen volume, mass activity, initial motility, sperm concentration, and abnormal sperm rate. The remainder of the semen samples of each bull were diluted to a concentration of 1:10 (semen:extender) with isotonic sodium citrate + egg yolk solution. The diluted semen samples were then divided into 12 sterile tubes of equal volume (0.5 ml). Different amounts of PGF2a [0 (PGF2a-free), 125, 250, 500, 1000, and 1500 µg] were added to 6 of these samples at 37 ¼C. Similarly, different amounts of metamizol [0 (metamizolfree), 125, 250, 500, 1000, and 1500 µg] were added to the other 6 samples at 37 ¼C. After the supplementation of PGF2a or metamizol, all semen samples were stored at 4 ¼C. The sperm motility of the samples was examined at 0, 1, 2, 4, 24, 48, 72, 96, 120, 144, 168, 192, and 216 h. No significant differences in spermatological characteristics were determined between the bulls. Sperm supplementation with 125 µg and 250 µg PGF2a caused a statistically significant increase (P < 0.05) in the motility of diluted semen stored at 4 ¼C after 24 h versus diluted PGF2a-free semen. However, the supplementation with 500 µg and 1000 µg PGF2a caused significant motility decreases after 4 h, while 1500 µg PGF2a also caused a decrease after 2 h compared to diluted PGF2a-free semen (P < 0.05). On the other hand, metamizol supplementation of 125 µg and 250 µg significantly decreased the motility of diluted semen stored at 4 ¼C after 48 hand 24 h, respectively, while 500 µg, 1000 µg, and 1500 µg of metamizol reduced motility after 4 h (P < 0.05) in comparison to the diluted metamizol-free semen. In conclusion, the addition of small amounts of PGF2a to diluted bull semen samples may help to maintain sperm motility during short-term storage at 4 ¼C.
Sulandırılmış Boğa Spermalarının Motilitesi zerine Prostaglandin F2a ve Metamizolun İn Vitro Etkileri
Makale - Yabancı Dilde Makale
Keywords: Bull semen PGF2a metamizol sperm motility